KONTROVERSI HADIS INNA ABῘ WA ABĀKA FĬ AL-NĀR (TELAAH SANAD DAN MATAN HADIS) - Prayitno, Mujahid Agil; Ikmal, Ikmal; Sulfa, Nafilah (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2025)
This study aims to explain the position of the hadith "innā abĭ waabāka fĭ al-nār" which is considered controversial. In this paper, the author focuses his research study from the side of takhrĭj hadith, analysis of sanad and matan hadith, and analysis of understanding hadith. This type of research is classified as library research. Through this study, the hadith "innā abĭ wa abāka fĭ al-nār" was takhrijed by three hadith scholars with different sanad lines. Each narrator has a connection between one and the other, and is classified as a trusted narrator and has strong memorization, from the side of the hadith editorial from the three lines there are slight differences that do not affect the degree of the hadith. From the side of understanding, scholars agree that the hadith has nothing to do with the condition of the Prophet Muhammad's parents with several reasons supported by authentic opinions.